Ambiente e comportamento informacional em decisões do saneamento básico: um estudo de caso na companhia de saneamento de Minas Gerais Copasa - Wilimar Junio Ruas (2015)
In recent years, sanitation has played a prominent role in brazilian society. Water scarcity and lack of water supply in urban centers, the proliferation of disease due to lack of sewage collection and its cost to the health system, flooding and its consequences in the cities due to the rains are some of the issues that they are directly related to the sanitation policies. In this context, it is necessary to understand how the information is used by professionals sanitation and how they seek to conduct their activities and problem solving. These professionals need information toassist them in decision-making for better management of the brazilian sanitation. The overall objective of this research is to describe and analyze the information behavior of the Company's Sanitation Minas Gerais (Copasa), with regard to the search and use of information sources in the decision-making process. For this purpose, it isdefined as specific objectives: to describe the information environment of Copasa; characterize seeking behavior and use of information for decision making by professionals; identify the sources of information most used by professionals and characterize them on the frequency of use, accessibility, relevance, reliability and contribution to decision making. Descriptive methodological nature, the research wasconducted through case study strategy, using as source of evidence to document analysis and a survey of qualitative and quantitative type. Data were collected through the Websurvey quiz sent to professionals, totaling 112 interviewed. Data were analyzed using descriptive statistics and correlation test between variables. The results allowed to characterize the Copasa's information environment based on components of the strategy, policy, culture and behavior, team, process and architecture-related information. Regarding the information behavior, it identified thatelectronic sources are the highest frequency of use, and assigned to it the criteria of increased accessibility and relevance among the categories of sources analyzed by setting up an information culture, technology driven. The documentary sources stood out for reliability, especially laws, resolutions and sector regulations. Correlations conducted showed that the frequency of use is directly related to the ease of particular source of access, as well as the relevance of a source is directly related tothe reliability of their information. As professionals sanitation need information for decision making, understanding the information environment and seeking behavior and use of sources of information can be guiding instruments in the development of tools and actions in the field of information management, specific to the basic sanitation.